2012
DOI: 10.1038/jcbfm.2012.105
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of Altered Neurovascular Coupling in Chronic Stroke Patients using Multimodal Functional MRI

Abstract: Evaluation of cortical reorganization in chronic stroke patients requires methods to accurately localize regions of neuronal activity. Blood oxygenation level-dependent (BOLD) functional magnetic resonance imaging (fMRI) is frequently employed; however, BOLD contrast depends on specific coupling relationships between the cerebral metabolic rate of oxygen (CMRO 2 ), cerebral blood flow (CBF), and volume (CBV), which may not exist following stroke. The aim of this study was to understand whether CBF-weighted (CB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
58
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(62 citation statements)
references
References 45 publications
3
58
1
Order By: Relevance
“…Similarly, wrist movement failed to increase the BOLD signal in the primary motor cortex in chronic stroke patients (13), suggesting impaired functional hyperemia in regions with increased functional activity. However, when cerebral blood flow and blood volume were assessed in response to functional activation using the more direct methods of arterial spin labeling (ASL) and vascular-space-occupancy-fluid attenuated inversion recovery, functional hyperemia was, in fact, maintained in the motor cortex after stroke (13). The reasons for the discrepancy between the results obtained with BOLD and ASL remain unclear.…”
Section: Neurovascular Regulation Ischemiamentioning
confidence: 99%
“…Similarly, wrist movement failed to increase the BOLD signal in the primary motor cortex in chronic stroke patients (13), suggesting impaired functional hyperemia in regions with increased functional activity. However, when cerebral blood flow and blood volume were assessed in response to functional activation using the more direct methods of arterial spin labeling (ASL) and vascular-space-occupancy-fluid attenuated inversion recovery, functional hyperemia was, in fact, maintained in the motor cortex after stroke (13). The reasons for the discrepancy between the results obtained with BOLD and ASL remain unclear.…”
Section: Neurovascular Regulation Ischemiamentioning
confidence: 99%
“…In the remaining 75% of patients, who exhibited some BOLD response, no correlation was found between the amplitude of the BOLD response and the degree of hypercapnic reactivity of the major arterial vessels, though impaired microvascular reactivity was thus not excluded. Moreover, Blicher et al [31] observed no BOLD signal change, on average, in M1 in response to unilateral isolated wrist extension-flexion in patients with residual paralysis, yet arterial spin labelling (ASL) and VASO-FLAIR (vascular-spaceoccupancy fluid attenuated inversion recovery) showed this task elicited CBF and CBV increases that were indistinguishable from those observed in control subjects [31].…”
Section: Mechanistic Basis Of Blood Oxygenation Leveldependent Functimentioning
confidence: 99%
“…69 For example, individuals with ischemic stroke can exhibit a blunted, exaggerated or reduced functional MRI BOLD signal during visual stimulation, with exaggerated or blunted hyperemia. 69 Although these data indicate a mismatch between CBF delivery and oxygenation extraction/metabolism, 69 the mechanisms explaining the variability in the functional MRI BOLD signal responses during visual stimulation are unknown.…”
Section: Human Neurovascular Couplingmentioning
confidence: 99%